(untitled) (Fenestella. Inside Medieval Art, 2022)
Since the early Middle Ages, the monastic presence in Piedmont found favourable and rather diversified areas in which to settle. The historiography of recent decades has begun to fine-tune the known data, although an overall vision is still struggling to emerge, beyond in-depth studies of specific sites. Starting from this starting point, and on the strength of the new findings that archaeology and the revision of written sources have produced on various contexts, it is the aim of this paper to attempt an overall reading of early Piedmontese monasticism. The aim is not to draw an exhaustive frame, which is not possible at the moment, but rather to define lines of development and suggest some ideas for thought for future research.